Footprints of Clinical Pharmacology in Turkey: Past, Present, and Future - AKICI, AHMET (ELSEVIER, 2020)
Clinical pharmacology is an interdisciplinary field that encompasses all components of the relationship between drugs and humans. All clinical pharmacology professionals aim to support an improved quality of drug-oriented health services by providing teaching, research, and routine health care services that ensure more tolerable and more effective, suitable, and cost-effective use of drugs. Subsections of clinical pharmacology include clinical trials, pharmacoepidemiology and drug use, pharmacovigilance, pharmacoeconomics, the rational use of medicines, pharmacotherapy consultation, drug monitoring, counseling to authorities and industry, pharmacogenetics, and other practices. By approaching these subsections as part of 3 main aspects of clinical pharmacology-education, research, and health care-this review aims to provide local and international practitioners with detailed information about clinical pharmacology practices in Turkey and to contribute to building the network of communication and collaboration. This review also aims to play an encouraging and pioneering role for Turkey's national community and other countries that have not yet made clinical pharmacology functional in improving the quality of health services, promoting the dissemination of rational use of medicines, helping the set-up of clinical pharmacology organizations, enhancing quantity and quality of the clinical pharmacology workforce, and increasing the infrastructural facilities. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Clinical pharmacology; Clinical trials; Education; Health care services; Rational use of medicines; PRESCRIBING SKILLS; PRESCRIPTION AUDIT; RATIONAL USE; PHYSICIANS; ATTITUDES; EDUCATION; LESSONS; DRUGS